Papilloedema and MRI enhancement of the prechiasmal optic nerve at the acute stage of Leber hereditary optic neuropathy. Issue 5 (11th May 2010) - Lamirel, Cédric; Cassereau, Julien; Cochereau, Isabelle; Vignal-Clermont, Catherine; Pajot, Olivier; Tanguy, Jean-Yves; Zanlonghi, Xavier; Reynier, Pascal; Amati-Bonneau, Patrizia; Dubas, Frédéric; Bonneau, Dominique; Verny, Christophe
Abstract : The authors report a case of one patient from a family carrying the homoplasmic Leber hereditary optic neuropathy (LHON) G11778A mitochondrial DNA mutation with papilloedema 9 months prior to the acute stage of LHON and still present at the onset of visual loss. During the vision loss, the MRI demonstrated a T2 hyperintensity and an enhancement of the prechiasmal left optic nerve, suggesting the existence of an inflammatory mechanism. A retrospective review of the chart of two others members of the same family, with bilateral optic disc oedema at onset of the vision loss, suggests that the relationship of papilloedema and acute phase of LHON may not be just a coincidence, at least in this family. The visual loss related to LHON could have been triggered in the setting of the chronic papilloedema, associated with the intracranial hypertension.